A Dual-Platform Laser Scanner for 3D Reconstruction of Dental Pieces. (December 2018) - Yang, Shuming; Shi, Xinyu; Zhang, Guofeng; Lv, Changshuo
Abstract: This paper presents a dual-platform scanner for dental reconstruction based on a three-dimensional (3D) laser-scanning method. The scanner combines translation and rotation platforms to perform a holistic scanning. A hybrid calibration method for laser scanning is proposed to improve convenience and precision. This method includes an integrative method for data collection and a hybrid algorithm for data processing. The integrative method conveniently collects a substantial number of calibrating points with a stepped gauge and a pattern for both the translation and rotation scans. The hybrid algorithm, which consists of a basic model and a compensation network, achieves strong stability with a small degree of errors. The experiments verified the hybrid calibration method and the scanner application for the measurement of dental pieces. Two typical dental pieces were measured, and the experimental results demonstrated the validity of the measurement that was performed using the dual-platform scanner. This method is effective for the 3D reconstruction of dental pieces, as well as that of objects with irregular shapes in engineering fields.